The Impact of Short-Form Content Consumption on the Development of Interest and Reading Resilience in Alpha Generation Children - Dina Wicun; Djamaluddin Perawironegoro (Ananda: Jurnal Pendidikan Anak dan Remaja, 2025)
This study aims to analyze the impact of short-form content consumption on reading interest and endurance among Generation Alpha children using a psychopedagogical approach. The research employed a qualitative method with a single case study design, focusing on an 8-year-old female elementary school student as the subject. Data were collected through naturalistic observation over six weeks and semi-structured interviews conducted in the third and sixth weeks with both the subject and parents. Thematic analysis was used to identify patterns related to reading behavior and the influence of short-form content consumption. The findings reveal that short-form content consumption significantly reduces reading interest through observational learning mechanisms that alter children's expectations toward information format, preferring content that is "fun and easy to understand." Additionally, reading endurance declined due to weakened delay of gratification abilities and attention system adaptation to rapid stimuli. The study concludes that this phenomenon represents cognitive adaptation to the digital environment rather than mere motivational issues, requiring strategic psychopedagogical interventions including gradual reading endurance training, self-regulation strengthening through mindfulness techniques, and educational approaches to limit short-form content consumption. These findings contribute to understanding the psychological mechanisms underlying digital media's impact on literacy development and provide practical implications for developing adaptive literacy approaches in the digital era.